Peculiarities of destruction mechanism of polymeric intumescent fire protective coatings - Mačiulaitis, Romualdas; Grigonis, Mindaugas; Malaiškienė, Jurgita; Lipinskas, Donatas (Journal of Civil Engineering and Management, 2018)
The article describes the destruction mechanism of intumescent fire protective paint coatings at the time of their aging under the impact of simulated climatic factors. Steel plates covered in anti-corrosion varnishes and intumescent fire protective paint coatings of several types and different composition were used in the research, while certain samples were also additionally covered in protective coatings protecting from environmental effects. SEM, DTA and FT-IR researches were conducted on control samples and samples after aging. Aging was performed in 3 ways: according to regimes I and II in the laboratory and having stored them for 12 months under the outdoor conditions under the roof. The aging mechanism of materials was determined to be very similar when using different methods of aging: with increasing number of cycles, the extent of damage to the surfaces and their diversity increase. In all cases, chemical material changes were observed after artificial aging cycles compared to control samples. In aged samples, there were some new connections occurring, while others changed or disappeared judging from the number of waves and intensity of peaks, which shows that certain compounds form, while others change and disintegrate under the influence of environmental heat and mass exchange.